Statistical Estimates of Social Inequality and Poverty in Ukraine - Osaulenko О. Н.; Herasymenko, S. S. (Statistics of Ukraine, 2015)
The objective of the study is to describe statistical methods for measurement of social inequality and poverty The complexity of statistical description of life standard and its components is emphasized at the beginning of the study First and foremost, it concerns organization of statistical survey and methods for aggregation of the collected data for computation of aggregated measure. It explains a wide gap between measures of the population’s life standard and its components like life satisfaction, produced by various organizations. This raises the need in improvement of statistical methodologies for the measurement, to produce more credible and reliable information. Bearing in mind the importance of solutions aiming to relieve social tensions, the study is focused on detailed analysis of the essence of social inequality and poverty, commonly used methods for their statistical measurement. Sources of statistical data that can be used for this purpose are described. In Ukraine, measurement and analysis of poverty level is made by use of the data collected in the household survey The survey program is supplemented by questions of sociological bearing. Thus, households’ self assessment of the welfare level is made by subjective estimates on the sufficiency of incomes for satisfaction of basic necessities, estimates on the constraints on consumer capacities due to shortage of money, and estimates on social self-identification. Yet, self-identification estimates of poverty level have a notable shortcoming implicit, in an essential feature of this method, which is subjectivity. Notable shortcomings are found in the majority of other indicators proposed for poverty measurement by various international institutions. It is emphasized that the measures of social inequality will have better credibility and reliability, when a set of causally linked statistical indicators is used, which would enable for making comparative analysis by population group and territory; for identifying the foremost factors that cause variations in the life standard of population groups; for setting up priority measures aimed at elimination of social inequality